Effect of polyethylene glycol on browsing behaviour and performance of late lactating goats - Decandia M.; Molle G.; Sitzia M.; Cabiddu A.; Ruiu A.; Pampiro F.; Pintus A. (Sheep and goat nutrition: Intake, digestion, quality of products and rangelands, 2000)
The effect of polyethylene glycol (PEG), an antitannic substance, on feeding behaviour, intake and milk production of Sarda goats at the end of lactation, was evaluated. Twenty goats were allowed to browse for 7 hours daily on 5 ha shrubland. The goats were allotted to two groups of ten: PS receiving 50 g per day of PEG 4000 MW, and PU, receiving no PEG supplementation. Feeding behaviour and feed intake were studied by direct observation, using the bite-count method. In vivo digestibility of dry matter and crude protein was assessed using C36 alkane as external marker. The time spent grazing was similar in the two groups. The average intake at pasture tended to be higher in PS than PU (1366 vs 1187 g DM per head per day, NS). The percentage of the species eaten by the goats was different in the two groups: the PEG supplemented goats ate more tanniferous species like Pistacia lentiscus L. whereas the control goats selected more herbaceous species.
8. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1998/09/03-05, Grignon (France)